Tourists’ perceptions regarding the use of anthropomorphic robots in tourism and hospitality - Christou, Prokopis A.; Simillidou, Aspasia; Stylianou, Maria C. (My University, 2020)
Purpose: Amidst the COVID-19 outbreak, service organizations rushed to deploy robots to serve people in quarantine, again igniting the ongoing dispute regarding robots in tourism. This study aims to investigate tourists’ perceptions regarding the use of robots and, more specifically, anthropomorphic robots in the tourism domain. Design/methodology/approach: A qualitative inquiry was used to delve deep into the issue of tourists’ perceptions regarding the usage of anthropomorphic robots in tourism, with a total number of 78 interviews with tourists being retained in the study. Findings: The findings reveal that tourists favor the use of anthropomorphic robots over any other type of robot. The use of anthropomorphic robots in tourism may result in an overall enhanced experiential value. Even so, informants also expressed frustration, sadness and disappointment vis-à-vis the use of robots in a human-driven industry. Research limitations/implications: A conceptual continuum of tourists’ perceptions and concerns over the use of robots is presented that can guide future studies. Tourism stakeholders may look at the possibility of incorporating carefully designed anthropomorphic robots in key service positions, but should not give the impression that robots are replacing the human face of the organization. Practical implications: Tourism stakeholders may look at the possibility of incorporating carefully designed anthropomorphic robots in key service positions, but should not give the impression that robots are replacing the human face of the organization. Originality/value: Tourism organizations that make use of robots run the risk of being perceived as nonanthropocentric. This leads to the conclusion that anthropomorphism could be used but should not replace the sector’s anthropocentrism. The study conveys tourists’ concerns over technological (robot) determinism.
Keywords: Anthropomorphism; Humanlike robots; Androids; Tourist perceptions; Technology